Wariacje na temat starości w opowiadaniach Brunona Schulza - Smusz, Aleksandra (Starość i młodość w literaturze i kulturze, 2016)
The article raises, so far overlooked in the gerontological literature, question of old age based on thecompositions: Pensioner, Loneliness and Sanatorium Under the Sign of the Hourglass by Bruno Schulz.According to the aforementioned concept, the author of The Cinnamon Shops unites poetic prose with broadly defined and still valid social issues. Schulz depicts the autumn of life as having numerous faces— it is associated with various experiences such as returning to childhood and youth at all costs, loneliness, lack of care and interest on the part of loved ones, finally leading to isolation and social exclusion. However, the writer describes these aspects without any pathos, often using irony and reviving presented images with a use of fantastic elements.